FAKTOR-FAKTOR YANG MEMPENGARUHI INCOME SMOOTHING PADA PERUSAHAAN INDUSTRI PERBANKAN YANG TERDAFTAR DI BEI - Shintya Shasha Narita, Vidyarto Nugroho (Fakultas Ekonomi, Universitas Tarumanagara, 2020)
The purpose of this study is to obtain empirical evidenceabout the effect of firm size, leverage, profitability, board size, and cash holdings on income smoothing in banking industry companies listed on the Indonesia stock exchange for the period of 2016-2018. This study uses 31 samples of banking industry companies selected based on the purposive sampling method. The data used was secondary data in the form of financial statements originating from www.idx.co.id and www.sahamok.com with a total sample of 93 company data processed using SPSS 23.0. Data are being analyzed using logistic regression analysis with the SPSS 23.0 program. The results showed that leverage and cash holdings have a significant positive influence on income smoothing, board size have a significant negative influence on income smoothing. While the firm size and profitability has no influence on the income smoothing.